Correction to: Is vitamin C enough? A case report of scurvy in a five-year-old girl and review of the literature - Timothy Hahn; Whitney Adams; Keith Williams (BMC, 2019)
Following publication of the original article [1], the authors reported that an out-of-date version of Figure 1 had been incorporated in the published article.